(Re-)Framing the Arab/Muslim Mediating Orientalism in Contemporary Arab American Life Writing - Schmidt, Silke (Edition Kulturwissenschaft, 2014)
Media depictions of Arabs and Muslims continue to be framed by images of camels, belly dancers, and dagger-wearing terrorists. But do only Hollywood movies and TV news have the power to frame public discourse? This interdisciplinary study transfers media framing theory to literary studies to show how life writing (re-)frames Orientalist stereotypes. The innovative analysis of the post-9/11 autobiographies 'West of Kabul, East of New York', 'Letters from Cairo', and 'Howling in Mesopotamia' makes a powerful claim to approach literature based on a theory of production and reception, thus enhancing the multi-disciplinary potential of framing theory.